EVALUASI PENGEMBANGAN SUMBER DAYA MANUSIA PADA DINAS TANAMAN PANGAN DAN PETERNAKAN PROVINSI SULAWESI TENGGARA - Aliddin, Laode Asfahyadin (Jurnal Manajemen dan Kewirausahaan, 2022)
This research aims to evaluate human resource development practices at the Food Crops and Livestock Service of Southeast Sulawesi Province. This research uses a qualitative approach by describing the research respondents' arguments regarding the choice of statements and the frequency distribution of respondents' statements from the data that has been collected. Data was obtained from 78 respondents who were Civil Servants (PNS) at the Food Crops and Livestock Service of Southeast Sulawesi Province. The data analysis method for this research uses descriptive analysis. The results of the research show that the human resource development practices implemented at the Southeast Sulawesi Province Food Crops and Livestock Service, in terms of education and training, career development, empowerment and work involvement, have been implemented well.